Smoking Households Give Less to Charity. (June 2020) - Siahpush, Mohammad; Tibbits, Melissa; Maloney, Shannon; Johansson, Patrik; Grimm, Brandon; Nguyen, Minh; Soliman, Ghada A.; Wani, Rajvi J.; Singh, Gopal K.
This study had two aims: (a) to assess, among households in the United States, the association between spending money on cigarettes and participation in charitable giving, and between spending money on cigarettes and amount spent on charitable giving, and (b) to assess whether the association between smoking and charitable giving is mediated by religiosity, social capital, cognitive aptitude, and happiness. To address these aims, we used data from Consumer Expenditure Interview Survey and Midlife in the United States Survey. The analyses revealed that households that spend money on cigarettes are less likely to participate in charitable giving. Furthermore, among households who do give to charity, smoking households give a lesser amount than others do. Religiosity, social capital, cognitive aptitude, and happiness do not appear to mediate the relationship between smoking and charitable giving.